2005
DOI: 10.1109/tnsre.2005.857687
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of signals from a chronically implanted, silicon-based electrode array in non-human primate primary motor cortex

Abstract: Multiple-electrode arrays are valuable both as a research tool and as a sensor for neuromotor prosthetic devices, which could potentially restore voluntary motion and functional independence to paralyzed humans. Long-term array reliability is an important requirement for these applications. Here, we demonstrate the reliability of a regular array of 100 microelectrodes to obtain neural recordings from primary motor cortex (MI) of monkeys for at least three months and up to 1.5 years. We implanted Bionic (Cyberk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
353
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(385 citation statements)
references
References 26 publications
30
353
0
1
Order By: Relevance
“…First, long term viability is questionable. While in some cases, implants seem to last for years, in others they become unusable after just a few months [5,75,77,68]. Because of the widely varied results within studies, more thorough investigation is needed, with more tightly monitored controls, to determine long term viability and possible reasons for variation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, long term viability is questionable. While in some cases, implants seem to last for years, in others they become unusable after just a few months [5,75,77,68]. Because of the widely varied results within studies, more thorough investigation is needed, with more tightly monitored controls, to determine long term viability and possible reasons for variation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies [75] have shown that day to day fluctuations occur within the consistency of a signal waveform and patterns, as well as signal viability. Harris et al suggest that this is largely due to either human operator error or wrongful attribution of spikes to certain neurons [76].…”
Section: Signal Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies however, demonstrating long term biocompatibility of microelectrodes. Suner et al reported no evidence of SNR change and a poor relationship between impedance and SNR during long term microelectrode recordings (Suner et al, 2005). The carrier, or insulating agents encapsulating the wire electrodes can be important in this process.…”
Section: Stability Of Unit Recordingsmentioning
confidence: 99%